Treatment of osteopetrosis combined with fracture around femoral internal fixation: a case report - Xu, Xiaoping; Li, Tao (Frontiers in Surgery, 2025)
Osteopetrosis is a rare disease caused by bone resorption disorders due to a decrease in osteoclasts or functional abnormalities, which can easily lead to secondary fractures. Currently, there are few reports on the treatment of fractures around internal fixation in such patients. Here, we report on the treatment experience of a rare case of a patient with osteopetrosis who suffered a fracture around the internal fixation of the right femur. A 59-year-old female patient suffered a right femoral intertrochanteric fracture in 2014 and was diagnosed with osteopetrosis. She underwent right femoral intramedullary nailing surgery. In October 2021, the patient sustained a fracture around the internal fixation device of the right femur due to a fall. We performed surgery to remove the intramedullary nail device and conducted a second internal fixation surgery using a longer intramedullary nail. During follow-up, the patient's recovery was satisfactory. Imaging studies at one year postoperatively showed good healing of the femoral shaft fracture. After more than three years of follow-up, the patient has returned to normal daily activities. Reviewing this case, we found that detailed preoperative planning, appropriate surgical techniques and internal fixation selection, and meticulous intraoperative procedures are key to treating such patients. Additionally, ensuring the safe removal of internal fixation is of critical importance.